Validação de um método multianalito para determinação de micotoxinas e pesticidas em arroz usando metodologia de extração dilute and shoot e UHPLC-MS/MS - Lucas Pinto da Silva (2017)
The present work describes the development and validation of an analytical procedure for the simultaneous determination of pesticides of different classes and of mycotoxins without rice (this type of sample was used as representative matrix for cereals and foods with low moisture content). The sample preparation protocol was based on a one-step extraction procedure with a solution of acetonitrile and acidified water without further cleaning steps. This simple process of dilution and burning efficiently extracted the chemical compounds from rice samples, a very complex food matrix. The analyzes were performed using ultra high performance liquid chromatography coupled with sequential mass spectrometry (UHPLC-MS/MS). The mass spectrometer operated in negative and positive modes. Two m/z transitions were chosen for each analyte. A chromatographic run was 7 minutes. Validation was adopted following the recommendations of Manual de Garantia da Qualidade Analítica, SANCO/12571/2013 and 2002/657/CE. Thus, a recovery of fortified white samples was calculated to estimate an accuracy, which remained between 70 and 110%. The precision, shown as the standard deviation, was estimated under the conditions of repeatability/reproducibility and was compared with the expected values obtained by the Horwitz function. The quantification limits were established for all analytes and were consistent with those established by the regulations. Finally, the uncertainties associated with the analytical results were estimated using a button-up methodology. It is concluded that the present methodology can be applied efficiently to determine mycotoxins and pesticides in a matrix as complex as rice in a simple, efficient and reliable way. The validation results indicate that this methodology is within the laws and restricts worldwide. Finally, it can be considered that the analytical treatment can be expanded to be applied to the analysis of other pesticides and mycotoxins and other matrices.